Peran Wattpad dalam Meningkatkan Minat Membaca Sastra di Kalangan Remaja - Anita Yuliani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study explores the role of the digital platform Wattpad in enhancing literary reading interest among teenagers. In the current technological era, adolescents are more inclined to engage with digital media rather than printed materials. Wattpad, an online reading and writing application, has emerged as a widely used platform among young readers. The aim of this study is to examine the extent to which Wattpad influences reading habits, identify the factors that make it appealing, and analyze its contribution to introducing literature to the younger generation. The research adopts a qualitative approach through literature review methods. Data were collected from various relevant academic sources and analyzed using content analysis techniques. The findings indicate that Wattpad effectively increases adolescents' reading interest through accessible content, relatable themes, and interactive features. Moreover, Wattpad can serve as a creative and engaging medium for teaching literature within educational settings. This study suggests that digital platforms like Wattpad should be more widely incorporated into literary literacy programs, and future research should include field observations to obtain a deeper understanding of the impact on reading behavior